2007
DOI: 10.1152/ajpgi.00068.2007
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte growth factor promotes colonic epithelial regeneration via Akt signaling

Abstract: Hepatocyte growth factor (HGF) can promote the regeneration of injured organs, including HGF gene therapy by electroporation (EP) for liver injury. In this study, we investigated the effect of HGF on dextran sulfate sodium-induced colitis and tried to clarify the regenerative mechanisms of colonic epithelial cells and the signaling pathway involved. Colitis was induced by dextran sulfate sodium in mice, together with HGF gene transfer by EP. On day 10, the colitis was evaluated histologically and by Western bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 43 publications
1
17
0
1
Order By: Relevance
“…[29][30][31] Each of these factors has been described earlier as facilitating intestinal mucosa repair, either through enhancement of cell proliferation or inhibition of epithelial cell apoptosis, or by a combination of both. [32][33][34][35] The therapeutic benefit of MSC reported in this study could be the consequence of releases and synergic effects of multiple paracrine factors. Further research is needed to elucidate this complex issue.…”
Section: Discussionmentioning
confidence: 76%
“…[29][30][31] Each of these factors has been described earlier as facilitating intestinal mucosa repair, either through enhancement of cell proliferation or inhibition of epithelial cell apoptosis, or by a combination of both. [32][33][34][35] The therapeutic benefit of MSC reported in this study could be the consequence of releases and synergic effects of multiple paracrine factors. Further research is needed to elucidate this complex issue.…”
Section: Discussionmentioning
confidence: 76%
“…These results demonstrated that sprouty-2 induces an increase in functional c-Met in colon cancer cells. Important down-stream effectors of c-Met includes phosphatidylinositol-3kinase (PI3K/Akt) and mitogen-activated protein kinase (MAPK)/extracellular signal-regulated kinase (ERK) that mediate proliferative and pro-survival signals (Kanayama et al, 2007). In colon cancer cells Akt and ERK enhance cell cycle progression and inhibit apoptosis (Vaculova et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Hanawa et al (22) reported that administration of the naked HGF gene into the liver attenuated acute colitis in mice, and Kanbe et al (23) showed that intrarectal administration of a plasmid carrying the HGF gene ameliorated DSS-induced colitis in mice. Kanayama et al (24) found that colonic epithelial regeneration is promoted by HGF gene transfer via electroporation. Oh et al (43) reported that HVJ liposomes encapsulating the hHGF gene ameliorated TNBS-induced colitis in mice, and that intrarectal administration of an Ad carrying the HGF gene improved colonic damage in TNBS-induced colitis (21).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Hanawa et al (22) demonstrated the attenuation of mouse DSS colitis by naked gene transfer of rat HGF into the liver, and Kanbe et al (23) reported the amelioration of mucosal damage in DSS colitis by the intrarectal administration of the naked HGF gene. In their study, Kanayama et al (24) demonstrated the promotion of colonic epithelial regeneration by HGF gene transfer through electroporation. Findings by those authors suggest that HGF is potentially an important new treatment modality for promoting the repair of intestinal mucosa in patients with IBD.…”
Section: Introductionmentioning
confidence: 99%